Dosimetry Study in Head and Neck of Anthropomorphic Phantoms in Computed Tomography Scans - Alvaro Mauricio Ladino Gomez; P. C. Santana; A. P. Mourão (Ital Publication, 2020)
Objectives: To determine the CT absorbed dose profiles for routine adult scan parameters in adults, using male and female anthropomorphic phantoms. Compare the levels of absorbed dose of the phantoms and perform image quality analysis by making noise percentage measurements on the CT images obtained. Methods: Radiochromic film strips were introduced in the central region of the phantoms for to record the dose profile in head and neck in order to determine the amount of the dose deposited along the central axis of the phantoms. The scans were performedon a 64 - channel CT scanner (General Electric), programmed in helical scaning mode. In addition to the routine acquisition protocol with fixed current value, it was performed other three scans with the voltage of 80, 100 and 120 kV, using automatic exposure control. Results: Absorbed dose values were found between 15.54 to 24.38 mGy on average for anthropomorphic male phantom and values of 13.13 to 21.49 mGy for anthropomorphic female phantom. Noise analysis was performed, finding that all are acceptable diagnostic parameters according to ministerial order 453/98 of the Brazilian Ministry of Health.  The acquisition parameters of CT images were found that deposited on average less doses in the head and neck for both phantoms, maintaining the image quality for diagnosis.